Distance, Travel Time and the Availability of Services with Antenatal Visits - elin supliyani (Jurnal Informasi Kesehatan Indonesia (JIKI), 2017)
Abstract: Antenatal care is one of the most effective health interventions for preventing morbidity andmaternal and infant mortality, especially in places with the poor general health status of the mother.Accelerating decline in MMR done by increasing the coverage of antenatal care. Therefore, research isneeded to analyze the relationship of distance, travel time and the availability of services with antenatalvisits in the region. This study is cross cut by analytical design correlative. Data were analyzed usingchi-square test. The results showed that 94 mothers (47%) visited antenatal <4 times and 106 (53%) Â³4 times. Mothers who antenatal <4 times, 65% of the distance to the place of service> 2 km, 55% oftravel time to the service of> 25 minutes, and 54% said lack of service availability. The analysis showedthat distance and time had a significant association with the antenatal visit (p = 0.016, p = 0.043), aswell as the availability of services has a significant association with antenatal care visit in PuskesmasCijeruk (p = 0.030).